ANALISIS TEKNOLOGI BLOCKCHAIN PADA CYBERSECURITY DI BIDANG AKUNTANSI: SISTEMATIK LITERATUR REVIEW - Alvina, Yulianissa; Sridayanti, Wiska; Azzahra, Nabila (Jurnal Riset Akuntansi, 2024)
In the digital era, cybersecurity has become a primary focus due to increasingly complex threats. Blockchain technology, promising high levels of security, has garnered attention in the field of cybersecurity and opened up new opportunities in the world of accounting. However, the success of blockchain-based accounting practices also raises concerns related to overall security. This research utilizes a Systematic Literature Review (SLR) to understand the integration of blockchain in safeguarding data security, particularly in the context of accounting. The research findings indicate that the Internet of Things (IoT) is a primary focus within the theme of blockchain in cybersecurity, with a positive impact on the efficiency and accuracy of financial data management. However, vulnerabilities to Distributed Denial of Service (DDoS) and Sybil Attacks in blockchain technology underscore the need for innovation in developing more robust security solutions in the field of accounting. Therefore, the implications of this research are to support the development of proactive blockchain security solutions against dynamic cyber threats, ensuring the integrity of financial data and the sustainability of company operations in an increasingly advanced digital era.